Squamous cell carcinoma of the tongue in Sprague-Dawley rats using 4-nitroquinoline 1-oxide model - Erfan, Erni; N., Nafrialdi; Ekawuyung, Puspita (Padjadjaran Journal of Dentistry, 2016)
Background. 4-nitroquinoline 1-oxide (4NQO) is a water soluble carcinogen which is often used to induce cancer in oral cavity. Objective. The purpose of this study was to know the incidence of histopathological lesions in the tongue of rats after administration of 4-nitroquinoline 1-oxide (4NQO) for a model of oral carcinogenesis in the animal experimental laboratory. Materials and Methods. This study was conducted in the Department of  Pathological Anatomy, Faculty of Medicine, University of Indonesia (FMUI). 4NQO (30 ppm) was administered by drinking water ad libitum to the Sprague Dawley (SD) rats during different time inductions (4-9 and 36-46 weeks). The present of tumor in oral cavity of the 4NQO-treated rats were observed macroscopically and microscopically. Tumor volume were measured based on the formula established by G. Carlsson. The degree of histological changes was determined according to observation towards their Hematoxylin and Eosin (HE) staining results. Results. Dysplasia and invasive squamous cell carcinoma (SCC) were respectively found in the tongue of the group given 4NQO for 4-9 and 36-46 weeks. The tongue from rats (4NQO for 36-46 weeks) exhibited whitish protuberant nodular lesions with the longest diameter was 17 mm. The histopathological lesion incidences for dysplasia and invasive SCC respectively were 25% (5/20) and 75% (15/20). The rats had tumor in their tongues with variation of degree alteration which proportional to the induction time. The extension of 4NQO induction time increasing the degree of change in the tumor. Conclusion. 4NQO represents a good model of carcinoma of tongue and gives consistence results with histological changes degree being related to duration of exposure.